The cultural ecology of Alaskan indigenous hip hop: “Ix̱six̱án, Ax̱ Ḵwáan (I Love You My People)” - Balestrini, Nassim (Ecozon@: European Journal of Literature, Culture and Environment, 2022)
In hip-hop studies, Indigenous rap music has been garnering increasing attention alongside other non-mainstream manifestations of this ‘glocal’ genre, and the field has begun to address the significance of specific locales for artistic expression. Worried about environmental studies research that extracts ecological insights from Indigenous cultures without paying attention to colonial history, Indigenous scholars have been critiquing how non-Indigenous colleagues frequently misconstrue the myriad ways in which place, language, knowledge, and cultural identity are intertwined in tribal cultures. Bringing these discourses into conversation, this article focuses on three music videos produced as part of the Native Connections program of the Tlingit and Haida’s Tribal Family and Youth Services department in 2018 and 2019. These videos, which feature the Juneau-based rappers Arias Hoyle and Chris Talley alongside other Indigenous adolescents, verbally and visually convey an understanding of their environment not as mere setting, but rather as a source of cultural-historical knowledge and current intergenerational cultural practice. Both location and language are showcased as repositories of cultural identification. The juxtapositions of seemingly untouched landscapes and settled cityscapes as well as of English and Tlingit can be read as confirming ecocritical theories that emphasize the ways in which cultural products address seemingly dichotomous elements such as nature/culture as interdependent. The hip-hop lyrics and videos examined here balance awareness of the historical baggage of settler-colonialism with the intellectually and spiritually invigorating celebration of a locally rooted Indigenous identity, which is neither stuck in the past nor unaware of the world at large. These works thus participate in the “cultural ecology” (Hubert Zapf) of hip hop by mapping out an artistic place defined by Alaskan Indigenous—and especially Tlingit—culture and community in Juneau, without losing sight of larger ...